2013
DOI: 10.1002/jmv.23520
|View full text |Cite
|
Sign up to set email alerts
|

Serologic evidence of avian influenza virus infections among Nigerian agricultural workers

Abstract: Nigeria has had multiple incursions of highly pathogenic avian influenza A (HPAI) H5N1 virus into its poultry population since 2006. This study aimed to determine if Nigerians exposed to poultry had evidence of avian influenza virus transmission to man. Between 2008 and 2010, 316 adult farmers and open market workers and 54 age-group matched, non-animal exposed controls were enrolled in a prospective, population-based study of zoonotic influenza transmission in four towns in southeastern Nigeria. Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…In this group, one bird that never shed detectable virus had low HI levels. (Blair et al, 2013;Huang et al, 2013;Liu et al, 2009;Okoye et al, 2013;Pawar et al, 2012;Uyeki et al, 2012;Zhou et al, 2014). On days 4 and 6 p.i., three DI quail per group were euthanized and lung samples were collected for virus titration.…”
Section: Effects Of Ferret-adapted Mutations On H9 Iavsmentioning
confidence: 98%
“…In this group, one bird that never shed detectable virus had low HI levels. (Blair et al, 2013;Huang et al, 2013;Liu et al, 2009;Okoye et al, 2013;Pawar et al, 2012;Uyeki et al, 2012;Zhou et al, 2014). On days 4 and 6 p.i., three DI quail per group were euthanized and lung samples were collected for virus titration.…”
Section: Effects Of Ferret-adapted Mutations On H9 Iavsmentioning
confidence: 98%
“…During the same period, a newly emergent avian H10N8 virus, also with six H9N2-like internal genes, was reported to cause fatal human infections in China (4). In the meantime, H9N2 viruses continued to cause human infections in China and other countries based on etiological and serological evidence (5)(6)(7)(8)(9)(10)(11)(12). We recently found that avian H9N2 viruses have undergone significant genetic evolution, especially in their internal genes, to form a predominant genotype (G57), which in turn provided the internal genes to multiple new subtypes, including H7N9 and H10N8 viruses (13).…”
mentioning
confidence: 99%
“…Gray et al also found neutralising antibodies to H6N2 and H7N2 influenza virus in the same study, but the prevalences were not significantly different between the exposed group and non-exposed controls (1.4 vs 4.0% and 5.5 vs 0%) [63]. Five other studies failed to find serological evidence of H6 or H7 exposure [18,63,80,102,117]. Only one-cross sectional study looked at H7N9 exposure, finding a seroprevalence of 6.3% in poultry workers in Guangdong, China, and a significantly lower percentage in non-exposed controls (0%) [110].…”
Section: Resultsmentioning
confidence: 95%
“…Gray et al found a significant difference in the seroprevalence of H5N2 antibodies in a swine- and poultry-exposed rural population from Iowa, United States, vs unexposed controls from the same region (8.8 vs 0%) [63]. Okoye et al found H5N2 antibodies in poultry-exposed and -unexposed groups from Nigeria (0.3 vs 1.8%), however, this difference was not significant [63,102]. Moreover, two studies executed in Romania and Vietnam found no antibodies in either group [18,91].…”
Section: Resultsmentioning
confidence: 99%